1995
DOI: 10.1099/0022-1317-76-1-113
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of human cytomegalovirus glycoprotein B (gpUL55) with mutagenized carboxy-terminal hydrophobic domains

Abstract: Stable transfectants were selected from human astrocytoma cells (U373) after transfection with recombinant expression vectors carrying the human cytomegalovirus (HCMV) glycoprotein B (gB; gpUL55) gene with alternative deletions of hydrophobic domain segment 1 (hdl) or segment 2 (hd2) of the carboxy-terminal potential bipartite membrane anchor domain. Comparative analysis of HCMV gB forms from cell lines gB(Mhdl) and gB(Mhd2), expressing mutagenized gB, and those from ceils expressing authentic gB showed that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
2
32
2
Order By: Relevance
“…For this study, stable transfectants of U373 described previously (Reis et al, 1993 ;Bold et al, 1996 ;Reschke et al, 1995), expressing either authentic HCMV gB or derivatives thereof with various deletions, were used. Transfectants gB(Mhd1) and gB(Mhd2) expressed gB derivatives with deletions of hydrophobic domains, hd1 and hd2, in the carboxy-terminal portion of the molecule (Reschke et al, 1995) ; hd2 of HCMV gB has been shown previously to be essential as well as sufficient for membrane anchoring.…”
Section: Nuclear Translocation Of Mutagenized Forms Of Human Cytomegamentioning
confidence: 99%
“…For this study, stable transfectants of U373 described previously (Reis et al, 1993 ;Bold et al, 1996 ;Reschke et al, 1995), expressing either authentic HCMV gB or derivatives thereof with various deletions, were used. Transfectants gB(Mhd1) and gB(Mhd2) expressed gB derivatives with deletions of hydrophobic domains, hd1 and hd2, in the carboxy-terminal portion of the molecule (Reschke et al, 1995) ; hd2 of HCMV gB has been shown previously to be essential as well as sufficient for membrane anchoring.…”
Section: Nuclear Translocation Of Mutagenized Forms Of Human Cytomegamentioning
confidence: 99%
“…During our recent functional analysis of the prominent hydrophobic domains in the C-terminal portion of HCMV gB (hdI, aa 714-747; hd2, 751-771) we observed that hd2 was essential as well as sufficient for membrane anchoring (Reschke et al, 1995). Sequence alignments of hdl, on the other hand, with established fusogenic domains of envelope glycoproteins of entirely unrelated viruses revealed an intriguing similarity (Reschke et al, 1995) implying that hdI may directly participate in the fusion event.…”
mentioning
confidence: 99%
“…Sequence alignments of hdl, on the other hand, with established fusogenic domains of envelope glycoproteins of entirely unrelated viruses revealed an intriguing similarity (Reschke et al, 1995) implying that hdI may directly participate in the fusion event.…”
mentioning
confidence: 99%
See 2 more Smart Citations